KEUNTUNGAN USAHA PENGOLAHAN KARET (Hevea brasiliensis L) SIT ASAP RSS (Rubber Smoke Sheet) DI DESA SIMPANG TIGA MATARAMAN KABUPATEN BANJAR - Rohansyah; Subhan Fitriadi (Fakultas Pertanian UVAYA Banjarmasin, 2022)
The purpose of this research is to know the revenue,the total cost,income and Profit of make Rubber Smoke Sheet farming . This research was conducted in Oktober 2022 at village Simpang Tiga, Mataraman, Banjar regency province South Kalimantan . The Purposive sampling metode used was by observing 23 farmers in Simpang tiga mataraman who.make rubber smoke sheet. The Average result of the revenue is Rp. 5.328.260,87/ farmer, the average total cost is Rp. 2.361.588,27/farmer, and total profit is Rp 2.966.672,60/farmer. Based on the Profit,we can know the From this result of development of farming make Rubber Smoke Sheet we believe that it has good prospect and revenue, profit and income ,tecnicall and economically